ID: 30. Issue 1 (November 2015) - Zaritsky, Luna; Bedsaul, Jacquelyn; Zoon, Kathryn
<x xml:space="preserve">Abstract</x> Type I interferons (IFNs) are induced upon viral infection and important mediators of innate immunity. While there is 1 IFN-<alternatives><inline-graphic xlink:href="ark:/27927/pgj2n6x7knr" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />β</alternatives> protein, there are 12 different IFN-<alternatives><inline-graphic xlink:href="ark:/27927/pgj2n6x7kqv" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />α</alternatives> subtypes. It has been reported extensively that different viruses induce distinct patterns of IFN subtypes, but it has not been previously shown how viral MOI can affect IFN induction. In this study, we discovered the novel finding that human U937 cells infected with 2 different concentrations of Sendai virus (SeV) induce 2 distinct type I IFN subtype profiles. Cells infected with a lower MOI induced more subtypes than cells infected with the higher MOI. We found that this was due to the extent of signaling through the IFNAR. The cells infected with the lower viral MOI induced the IFNAR2- dependent IFN-<alternatives><inline-graphic xlink:href="ark:/27927/pgj2n6x7kqv" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />α</alternatives> subtypes 4, 6, 7, 10 and 17, which were not induced in cells infected with higher virus concentrations. IFN-<alternatives><inline-graphic xlink:href="ark:/27927/pgj2n6x7knr" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />β</alternatives> and IFN-<alternatives><inline-graphic xlink:href="ark:/27927/pgj2n6x7kqv" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />α</alternatives> 1, 2 and 8 were induced in an IFNAR-independent manner in cells infected with both virus concentrations. IFN-<alternatives><inline-graphic xlink:href="ark:/27927/pgj2n6x7kqv" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />α</alternatives> 5, 14, 16 and 21 were induced in an IFNAR-dependent manner in cells infected with lower virus concentrations and in an IFNAR-independent manner in cells infected with higher virus concentrations. These results present the novel finding that different viral MOIs will differentially activate JAK/STAT signaling through the IFNAR, which greatly affects the profile of IFN subtypes that are induced.